2019
DOI: 10.1158/1538-7445.sabcs18-p2-08-38
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-08-38: Influence of prognostic factors on outcomes among metastatic breast cancer patients treated with CDK4&6 inhibitors in routine clinical practice

Abstract: Background: Evidence suggests that there are clinical features associated with a less favorable prognosis among patients with HR+/HER2- metastatic breast cancer (MBC) such as metastases to non-bone sites, including liver and lung, and negative progesterone receptor (PgR-) status. The objective of this study was to compare baseline characteristics and outcomes between those with and without these clinical factors among a cohort of HR+/HER2- MBC patients treated with a CDK4&6 inhibitor (CDK4&6i). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is less likely that patients with liver metastasis received CDK4 & 6 inhibitor-based therapies based on current prescribing patterns (Supplementary Table 1). The presence of liver metastasis is a risk factor for poor survival [40,41]. As a result, it may be that the estimated optimal treatment regimen favored CDK4 & 6 inhibitor-based therapies simply because patients with liver metastasis were underrepresented in this class and so led to improved survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is less likely that patients with liver metastasis received CDK4 & 6 inhibitor-based therapies based on current prescribing patterns (Supplementary Table 1). The presence of liver metastasis is a risk factor for poor survival [40,41]. As a result, it may be that the estimated optimal treatment regimen favored CDK4 & 6 inhibitor-based therapies simply because patients with liver metastasis were underrepresented in this class and so led to improved survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As the variable "Liver metastasis" was not present in the FHD, it was believed to have possibly been a potential unmeasured confounder in the main analyses. The SPD showed that presence/absence of liver metastasis was associated with survival [41,42]. Furthermore, liver metastasis status was unevenly distributed across regimen classes (with much lower prevalence among patients who received CDK4 & 6 inhibitor-based therapies; Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations